(Invited)Development of Plasma Atomic Layer Etching in Close-to-Conventional Etch Tools. (9th April 2018) - Cooke, Mike; Goodyear, Andy
Abstract : Plasma-based atomic layer etching is a cyclical etching process of gas dosing and ion bombardment that removes material layer by layer, and has the potential to remove single atomic layers with low damage. We consider how a conventional plasma etcher can be modiﬁed to perform this style of recipe and give results for Si and GaN/AlGaN. The need for precise control of ion bombardment energy and gas dose is highlighted, requiring specialized hardware.